Evaluation of open-face maxillary complete denture for patients with prominent premaxilla: a crossover study - Haitham A. Ismail; Muhammed B. El-Danasory; Salma Abolgheit; Ingy S. Soliman (BMC Oral Health, 2024)
Abstract Background The establishment of good facial esthetics is one of the main objectives of complete denture construction. Unfortunately, it may be the caused issue for patients having a prominent premaxilla due to excessive lip support by the labial flange of the maxillary denture. Open-face dentures (OFD) may suggest suitable prosthetic management for these patients. However, clinical evidence regarding the efficiency of OFD is scarce. Methods A total of 38 completely edentulous participants having prominent premaxilla and skeletal class I Angle’s classification were enrolled in this study. Each participant received a mandibular complete denture and 2 opposing maxillary dentures; conventional (CD) and open-face (OFD). On the day of denture insertion, the participants were divided into 2 groups; CD-OFD and OFD-CD where CD-OFD group was instructed to use the mandibular denture and the maxillary CD for 3 months and then to use the maxillary OFD for another 3 months after a wash-out period of 2 weeks. While group OFD-CD was instructed to use the mandibular denture and the maxillary OFD for 3 months then to use the maxillary CD for another 3 months after a wash-out period of 2 weeks. The dislodging force of the maxillary dentures was evaluated using the universal testing machine and the patient perception of retention, esthetics, and comfort was evaluated using the Visual Analogue Scale (VAS). Evaluation was carried out 1 day, 1 month, and 3 months after denture insertion. The Student t-test was used to compare the 2 maxillary dentures and the intervals for each denture were compared by using the ANOVA test with repeated measures followed by a Post Hoc test (adjusted Bonferroni) for pairwise comparison. Results The significance of the obtained results was judged at the 5% level (P value). The dislodging force and patient perception of retention did not show significant differences between the 2 dentures, while the perception of esthetics showed significant differences throughout the follow-up period. Perception of comfort showed an insignificant difference only at the 3-month interval. Conclusions Open-face maxillary dentures can be a suitable alternative for patients with prominent premaxilla to achieve satisfactory retention, aesthetics, and comfort.